Overview of the aeroponic agriculture – An emerging technology for global food security - Lakhiar, Imran Ali; Gao, Jianmin; Syed, Tabinda Naz; Chandio, Farman Ali; Tunio, Mazhar Hussain; Ahmad, Fiaz; Solangi, Kashif Ali (International Journal of Agricultural and Biological Engineering, 2020)
Traditionally, crops are cultivated in soil-based open field systems. Seasonality, environmental degradation, urbanization, and food security issues have replaced open-field systems with modern plant production systems. Soilless culture is one of the modern plant production systems, which involves much higher use of available resources. The presented study provides information about currently accessible soilless systems and discussed the aeroponic system. Compared to other soilless systems, aeroponic reduce water usage through continuous water circulation. However, the aeroponic is not entirely implemented among local farmers, and very few farmers have adopted the system due to the lack of research and technical information available in the literature. Therefore, this study was planned to provide information about the development and maintenance tasks required for practicing the aeroponic system. This study could provide knowledge to the researchers, farmers, and those people interested in practicing the aeroponic system.Keywords: aeroponic, food security, hydroponic, soilless culture, substrate cultureDOI: 10.25165/j.ijabe.20201301.5156Citation: Lakhiar I A, Gao J M, Syed T N, Chandio F A, Tunio M H, Ahmad F, et al. Overview of the aeroponic agriculture – An emerging technology for global food security. Int J Agric & Biol Eng, 2020; 13(1): 1–10.